Kerusakan ekosistem dan dampaknya terhadap keberlanjutan makhluk hidup - Evrianti, Hilda Aulia (Maliki Interdisciplinary Journal, 2026)
Ecosystem degradation is an increasingly complex global environmental problem that directly affects ecological balance and the sustainability of living organisms. Various forms of degradation, including deforestation, water and air pollution, land degradation, and climate change, have led to a significant decline in environmental carrying capacity across many regions. This study aims to examine the forms of ecosystem degradation, identify its main driving factors, and analyze the ecological, social, and economic impacts on the sustainability of living organisms, including humans and other species. The research method employed is a literature review by analyzing various scientific sources, environmental data, and relevant and credible previous studies. The findings indicate that human activities are the dominant cause of ecosystem degradation, particularly through uncontrolled exploitation of natural resources, environmental pollution, and large-scale land-use changes. These conditions result in biodiversity loss, disruption of food chains, increased frequency and intensity of natural disasters, declining public health quality, and weakening economic stability dependent on natural resources. Furthermore, ecosystem imbalance affects internal environmental processes, including biogeochemical cycles, degradation of soil and water quality, and reduced ecosystem resilience and self-recovery capacity. This study emphasizes the importance of ecosystem restoration and sustainable management through integrated reforestation, pollution control, bioremediation implementation, the use of environmentally friendly energy, and increased public awareness and active participation. Through integrated, systematic, and sustainable ecosystem management, environmental balance can be restored to support the sustainability of life for present and future generations.